2013
DOI: 10.1371/journal.pone.0060521
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis by Deep Sequencing of the Probiotic Lactobacillus brevis KB290 Harboring Nine Plasmids Reveals Genomic Stability

Abstract: We determined the complete genome sequence of Lactobacillus brevis KB290, a probiotic lactic acid bacterium isolated from a traditional Japanese fermented vegetable. The genome contained a 2,395,134-bp chromosome that housed 2,391 protein-coding genes and nine plasmids that together accounted for 191 protein-coding genes. KB290 contained no virulence factor genes, and several genes related to presumptive cell wall-associated polysaccharide biosynthesis and the stress response were present in L. brevis KB290 bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…Among the studied probiotic microbiota, lactic acid bacteria (LAB) are the most predominant, widely distributed and common inhabitants of epithelial surface of humans [2]. Several genera of LAB are widely used in fermented foods that are of traditional and industrial importance.…”
Section: Introductionmentioning
confidence: 99%
“…Among the studied probiotic microbiota, lactic acid bacteria (LAB) are the most predominant, widely distributed and common inhabitants of epithelial surface of humans [2]. Several genera of LAB are widely used in fermented foods that are of traditional and industrial importance.…”
Section: Introductionmentioning
confidence: 99%
“…lactis strains have been found to harbour several plasmids, which range in size from 2 to 80 kb (Davidson et al 1996). 17.9 kb Tolerance to oxidative stress Fukao et al (2013) For example, Lactoc. lactis SK11, a phage-resistant strain used in cheese making, contains four plasmids and was shown to have a substantial number of 'adaptation' genes (Siezen et al 2005).…”
Section: Plasmidmentioning
confidence: 99%
“…The draft genome of L. plantarum strain 16 contains more than eight plasmids, whereas nine plasmids were found in the completed genome of L. brevis KB290 (Crowley et al 2013;Fukao et al 2013). In L. brevis KB290, all of the plasmids had putative replication systems, including repABC genes for essential plasmid replication and stability, which is likely to explain the co-existence of multiple plasmids.…”
Section: Plasmidmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep sequencing of the whole genome of KB290 revealed it contains nine plasmids (Fukao et al . ). Plasmid‐curing experiments also demonstrated that pKB290‐1 is essential for resistance of the bacterium to gastrointestinal juice and for its tendency to aggregate.…”
Section: Introductionmentioning
confidence: 97%